2
$\begingroup$

I want to write the statement

$$\text{If } A^{-1} \text{ exists then } A^{-1} = \frac{\alpha-a}{\alpha^2-a^2}$$

using quantifiers. Note that $A$ and its inverse, if it exists, are taken from the set $\mathscr{G}$. My first thought is

$$ \exists B \in \mathscr{G}, BA = 1 \to B = \frac{\alpha - a}{\alpha^2 - a^2}$$

but this is incorrect because the antecedent needs to include the quantifier while here the grouping works out like so:

$$ \exists B \in \mathscr{G} \left( BA = 1 \to B = \frac{\alpha - a}{\alpha^2 - a^2} \right).$$

This is still true if $A^{-1}$ does not exist; in this case, there is simply no $B$ that satisfies the antecedent. But this is not the statement I'm looking for, because I need the quantifier in the antecedent. But the difficulty is that with the quantifier in the antecedent, there's no way to "instantiate" $B$ in the consequent:

$$ \left( \exists B \in \mathscr{G} , BA = 1 \right) \to \left( \underbrace{B}_\text{Not the same $B$.} = \frac{\alpha - a}{\alpha^2 - a^2} \right). $$

I believe that in first order logic you can say, "if there exists some $x$ satisfying these properties, then let this variable here be that $x$." How do I write that in this context?

$\endgroup$
  • $\begingroup$ The statement is about any $A $ in the set. So quantify $A $ first. Then if a $B $ exists, we have that $B=\dots $. And this is done. Everything is quantified and implication is clear. $\endgroup$ – AnyAD Jun 9 at 22:58
  • $\begingroup$ Is the inverse $B $ unique in your case ($B=A^{-1}\iff AB=I$)? $\endgroup$ – AnyAD Jun 9 at 23:08
  • $\begingroup$ @AnyAD Yes but I haven't proven so yet. $\endgroup$ – holomenicus Jun 10 at 19:54
2
$\begingroup$

Your statement is what is called a 'donkey-sentence', named after the rather violent example of:

'If a farmer owns a donkey, he will beat it'

Note how if you are asked to symbolize this one, you are likely to go through the same thought process you went through:

The first thought is that it is a conditional:

$\exists x \ \exists y (F(x) \land D(y) \land O(x,y)) \to B(x,y)$

But this doesn't work, since you have free variables in the consequent.

OK, but if you then pull the scope of the existential over the consequent, you get:

$\exists x \ \exists y ((F(x) \land D(y) \land O(x,y)) \to B(x,y))$

which doesn't work either, since this statement can be made trivially true by picking anything for $x$ that is not a farmer and/or anything for $y$ that is not a donkey, and hence the statement ends up saying little of interest at all.

The correct answer, of course, is to use a universal:

$\forall x \ \forall y ((F(x) \land D(y) \land O(x,y)) \to B(x,y))$

because the 'a' in 'a farmer' and 'a donkey' is really used as 'any'.

Similarly, the correct symbolization of our statement should be:

$$ \forall B \in \mathscr{G} \left( BA = 1 \to B = \frac{\alpha - a}{\alpha^2 - a^2} \right).$$

Now, you may still be wondering why you have a feeling that there should be an existential here.

Well, consider the following modified donkey-sentence:

'If a farmer owns a donkey, then we have a problem'

Now this sentence can be symbolized as:

$\exists x \ \exists y (F(x) \land D(y) \land O(x,y)) \to P$

Moreover, this turns out to be equivalent to:

$\forall x \ \forall y ((F(x) \land D(y) \land O(x,y)) \to P)$

So yes, there is a close connection between the use of the existential and the universal when conditionals are involved.

$\endgroup$
1
$\begingroup$

$$\forall A,B \in S ( (AB=I)\implies B=\dots )$$

Or you can write: for all $A $ in the set (( there is B in the set AB=I) therefore ($B=\dots$))

$\endgroup$
  • $\begingroup$ This proposition is just the same as the third one in my question. I need the quantifier in the antecedent, not quantifying the whole implication. $\endgroup$ – holomenicus Jun 10 at 1:33
  • $\begingroup$ What about $\exists B$ as you wrote? What is $B $ in the consequent (do you need to quantify $\alpha $,$a $)? I am affraid I don't really understand your question. $\endgroup$ – AnyAD Jun 10 at 2:23
1
$\begingroup$

You can actually just write $$A^{-1} = B \implies B = \frac{\alpha - a}{\alpha^2 - a^2}$$

since the equivalence will only be provable if $A^{-1}$ is defined.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.